Revitalisasi Organisasi melalui Perubahan Budaya - Dwi Irawati (Universitas Kristen Maranatha, 2004)
The culture of an organization is being viewed as an important determinant of its performance. We conceptualize organizational culture in terms of the degree of internal fit (cohesion and consistency) and in terms of the degree of external fit (linkages the strategy and the environment). Interaction between both determines the organization's performance.To get get started with cultural change to revitalize the organization, executives must have an accurate understanding of the current culture. Organizations that need to be success in their change of culture should run these things to minimize the scale resistance or lack of faith of the company and its employees, although this list carries no guarenteed: 1) return to the past for inspiration and instruction; 2)back to basic; 3)identify the principles that will remain constant; 4)find examples of success within the current culture; 5)promote hybridization; 6)label areas; 7)mourn the loss of cherished past. None of the actions mentioned was sufficient to produce all the changes a company sought.Finally, we need to stress that the change in the organization's culture does not come from merely agreeing on a new vision or honoring the past. It needs members' understanding of its value and their commitment to start and end the process of the cultural change in the organization. This means that we must first develop a deep appreciation for the historical and cultural roots of our organization, recognizing its realistic limitations and opportunities.Keywords: culture, cultural change, revitalize